MAGDEBURG LOGISTICS MODEL – THE SMART LOGISTICS ZONE AS A CONCEPT FOR ENABLING LOGISTICS 4.0 TECHNOLOGIES - Schmidtke, Niels; Glistau, Elke; Behrendt, Fabian (Advanced Logistic Systems - Theory and Practice, 2019)
Intelligent linking in the context of Industry 4.0 alters the objectives and possibilities of designing logistics solutions in the production economy today and tomorrow [1]. There is a growing need for an expanded theory of logistics that helps to characterize existing solutions as well as systematically develop new solutions and bring them together effectively and efficiently. The objectives are the development of a model of thinking and a procedure model for current and future logistics solutions including Logistics 4.0. The article explains the newly developed "Smart Logistics Zone" (SLZ). The SLZ is defined as a scalable examination and action area for analysis, evaluation, planning, control, regulation and (re-) configuration of logistics solutions [2]. New to the thinking model are the generation of solutions from (logistic) objects, pro-cesses, systems and the relevant infrastructure as well as the scalability of the considered zone. The framework model provides a quantifiable target system. The process model in turn allows a systematic solution development using method and technology databases. Several possible views on logistics, which are considered as aspects in the SLZ, are being elaborated. Other aspects of the presented concept such as intelligence and spatial categories are discussed as well. In the outlook a sample factory serves as a scalable examination area for the SLZ. In its application, the SLZ demonstrates a new perspective on the analysis, planning and evaluation of logistics systems. The approach is designed as a scalable tool. It can be adaptively applicable to various intralogistic and extralogistic problems. <em style="color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">This paper is a secondary publication of the article presented at the COMEC 2019 conference in Cuba, published with the permissions of the organization board of the conference and the authors.